2017
DOI: 10.1371/journal.pone.0182799
|View full text |Cite
|
Sign up to set email alerts
|

Point-prevalence survey of healthcare facility-onset healthcare-associated Clostridium difficile infection in Greek hospitals outside the intensive care unit: The C. DEFINE study

Abstract: BackgroundThe correlation of Clostridium difficile infection (CDI) with in-hospital morbidity is important in hospital settings where broad-spectrum antimicrobial agents are routinely used, such as in Greece. The C. DEFINE study aimed to assess point-prevalence of CDI in Greece during two study periods in 2013.MethodsThere were two study periods consisting of a single day in March and another in October 2013. Stool samples from all patients hospitalized outside the ICU aged ≥18 years old with diarrhea on each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…C. DEFINE, a multicenter study which aimed to assess pointprevalence of CDI in Greece, revealed a considerable prevalence of CDI in Greek hospitals ranging between 3.9 and 5.6 per 10,000 patient bed-days, and between 14.3 and 17.0% of hospitalized patients with diarrhea, respectively [6]. Our study is the first study of molecular characterization of C. difficile isolates in Greece across a large timeframe and attempts to cover a gap in knowledge in our region and other RTs for 027-lineage [7].…”
Section: Introductionmentioning
confidence: 99%
“…C. DEFINE, a multicenter study which aimed to assess pointprevalence of CDI in Greece, revealed a considerable prevalence of CDI in Greek hospitals ranging between 3.9 and 5.6 per 10,000 patient bed-days, and between 14.3 and 17.0% of hospitalized patients with diarrhea, respectively [6]. Our study is the first study of molecular characterization of C. difficile isolates in Greece across a large timeframe and attempts to cover a gap in knowledge in our region and other RTs for 027-lineage [7].…”
Section: Introductionmentioning
confidence: 99%